PENGARUH TERPAAN BERITA COVID-19 PADA PORTAL MEDIA ONLINE TERHADAP PENCARIAN INFORMASI KESEHATAN DI INTERNET - Qoirunischa Nandya Kusumaningrum (2021)
On December 31, the World Health Organization (WHO) announced that an outbreak of a new virus was discovered in Wuhan, China. The spread of the Corona Virus or Covid-19 continues by the media regularly. The need for health information is very important and needed by the community during a pandemic. The purpose of the study was to determine and measure the influence of exposure to covid-19 news on online media portals on searching for health information on the internet. The benefits of research are to contribute, especially in communication science and can be a reference for copywriters and contentwriters in making news, especially related to covid-19. Research using Information Search Theory. Research Methodology with quantitative explanation approach and survey method. The research population was 2064 university students on August 17, 1945. The sample used was Non Probability Sampling with Purposive Sampling technique which produced 95 respondents, by submitting 34 statements. The results showed a strong correlation with the number 0.543 with the consistency value of the health information search variable of 43,485, and the regression coefficient of the news exposure variable of 0.675. the coefficient of determination shows the value of R Square or the coefficient of determination of 0.223 if calculated based on the formula, it can produce a number of 22.3%. The results of the t test or hypothesis test based on the t value, namely t count of 5.172 > t table of 1.665, it can be said that H0 is rejected and H1 is accepted. The conclusion is that Information Seeking theory has been tested for assumptions and basic values in research phenomena. Suggestions that can be given to the public are to always select the information obtained, especially related to covid-19, for copywriters and contributors to consider content so as not to make people feel worried or uncomfortable related to covid-19 information